Associations of Proton-Pump Inhibitors and H2 Receptor Antagonists with Chronic Kidney Disease: A Meta-Analysis - Karn Wijarnpreecha (2018)
© 2017, Springer Science+Business Media, LLC. Background/Aims: The aim of this meta-analysis was to assess the risks of chronic kidney disease (CKD) and/or end-stage kidney disease (ESRD) in patients who are taking proton-pump inhibitors (PPIs) and/or H2 receptor antagonists (H2RAs). Methods: Comprehensive literature review was conducted utilizing MEDLINE and EMBASE databases through April 2017 to identify all studies that investigated the risks of CKD or ESRD in patients taking PPIs/H2RAs versus those without PPIs/H2RAs. Pooled risk ratios (RR) and 95% confidence interval (CI) were calculated using a random-effect, generic inverse variance method of DerSimonian and Laird. The protocol for this study is reg istered with PROSPERO (International Prospective Register of Systematic Reviews; no. CRD42017067252). Results: Five studies with 536,902 participants were patients were identified and included in the data analysis. When compared with non-PPIs users, the pooled risk ratio (RR) of CKD or ESRD in patients with PPI use was 1.33 (95% CI 1.18–1.51). Pre-specified subgroup analysis (stratified by CKD or ESRD status) demonstrated pooled RRs of 1.22 (95% CI 1.14–1.30) for association between PPI use and CKD and 1.88 (95% CI 1.71–2.06) for association between PPI use and ESRD, respectively. However, there was no association between the use of H2RAs and CKD with a pooled RR of 1.02 (95% CI 0.83–1.25). When compared with the use of H2RAs, the pooled RR of CKD in patients with PPI use was 1.29 (95% CI 1.22–1.36). Conclusions: Our study demonstrates statistically significant 1.3-fold increased risks of CKD and ESRD in patients using PPIs, but not in patients using H2RAs.